2022
DOI: 10.3390/cancers14041023
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Factor Repertoire of Breast Cancer in 3D Cell Culture Models

Abstract: Intratumor heterogeneity of breast cancer is driven by extrinsic factors from the tumor microenvironment (TME) as well as tumor cell–intrinsic parameters including genetic, epigenetic, and transcriptomic traits. The extracellular matrix (ECM), a major structural component of the TME, impacts every stage of tumorigenesis by providing necessary biochemical and biomechanical cues that are major regulators of cell shape/architecture, stiffness, cell proliferation, survival, invasion, and migration. Moreover, ECM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 213 publications
(225 reference statements)
0
9
0
Order By: Relevance
“…This may be explained by the differences between the materials, where the collagen more closely resembles the natural basal lamina, which maintains the integrity and the polarity of epithelial cells. This particular cell architecture formed on 3D models affects their intracellular signaling pathways including those involved in proliferation. …”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the differences between the materials, where the collagen more closely resembles the natural basal lamina, which maintains the integrity and the polarity of epithelial cells. This particular cell architecture formed on 3D models affects their intracellular signaling pathways including those involved in proliferation. …”
Section: Discussionmentioning
confidence: 99%
“…NUDT5 ( ENSG00000165609.13 ) was predicted by LightGBM and LASSO. It is reported to participate in the viral infection associated with signal transmission [ 44 , 45 ]. As for its specific role in association with COVID-19 compliments, the low expression level of the gene has been observed in severely infected cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been started in some research groups in parallel with organoid cultures, who are developing the isolation of cells and the optimisation of bioinks, developing protocols to print and culture patient-derived 3D structures, and comparing in vitro and in vivo drug sensitivity with therapeutic treatment results [78][79][80]. These models also have advantages and disadvantages, and in addition, there are several summaries and reviews about these subjects [21]. Our further aim is to investigate 3D bioprinted breast, glioma and ovarian TMS specimens as novel approaches for investigating drug responses in our next studies, with clinical collaboration (after obtaining ethical approval).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the recently developed 3D culturing technology and with 2D cell cultures and their drug sensitivity test results has shown that 3D models can more reliably show the in vivo characteristics of cancer cells. The reduced drug sensitivity of 3D cell cultures (mainly the same in vivo) [19] with reduced proliferation [20], altered gene expressions [21], morphology [22], and invasion [23] were described in many study models and tumour cell types dependently. Based on these findings, these systems can be suggested for the promotion of pharmaceutical developments and the testing of new drug candidates.…”
Section: Introductionmentioning
confidence: 99%